PARADIGMA STRUKTUR PERILAKU KINERJA PADA INDUSTRI SEPATU DI KABUPATEN MOJOKERTO - Savira Rahmadianti; Aris Soelistyo; Sri Budi Cantika (Jurnal Ilmu Ekonomi JIE, 2020)
This study aims to analyze the structure, conduct, and industrial performance at the Shoe Industry Center, Mojokerto Regency. This research method uses descriptive quantitative and qualitative, the population in this study is 30 units of the shoe business.The study was conducted by analyzing primary data, which was obtained from interviews with leather shoe entrepreneurs in the Mojokerto district. Data analysis was performed by regression. The independent variables used include Market Share (MS) to represent the structure, Capital, and Labor Ratio (CLR) to represent behavior and Price-Cost Margin (PCM) for a measure of industry profits.The results showed that the Market Share (MS) and Capital and Labor Ratio (CLR) variables had a positive and significant effect on the shoe industry variable, while the X-efficiency variable had a positive and significant effect on the shoe industry variable. From the results of this analysis, it could be detected that The existing market structure in the shoe industry in Mojokerto Regency is a type of market with intense oligopoly competition. This can be seen from the high value of food which can be indicated by the number of producers relative to market size, the heterogeneous types of goods.